Radar principles - Peebles, Peyton Z (John Wiley & Sons, 1998)
This volume fills a need in industry and universities for a comprehensive introductory text on radar principles. Well-organized and pedagogically driven, this book focuses on basic and optimum methods of realizing radar operations, covers modern applications, and provides a detailed, sophisticated mathematical treatment. Author Peyton Z. Peebles, Jr., draws on an extensive review of existing radar literature to.